2019
DOI: 10.1016/j.seizure.2019.01.020
|View full text |Cite
|
Sign up to set email alerts
|

“Breath holding spells” in a child with SCN8A-related epilepsy: Expanding the clinical spectrum

Abstract: A 14-month-old, developmentally-normal girl presented with daily events since 6-months of age. The events were characterized by crying (provoked by fall/anger) followed by cessation of crying, peri-oral cyanosis, and tonic stiffening of the limbs and jerking. She also had a microcytic/ hypochromic anemia. Initially she was diagnosed with breath-holding spells with reflex-anoxic seizures and started on iron with no effect. Subsequently, these episodes started happening without crying. On suspicion of seizures, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…In addition, when given iron supplementation, patients with BHS without IDA could show similar or even better response, as reported in previous studies (8,10). In contrast to the study of Jain et al (20), the present study found a significantly higher rate of complete remission with iron therapy in patients with a greater BHS frequency. The complete remission rate was 39.5% (53 patients).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In addition, when given iron supplementation, patients with BHS without IDA could show similar or even better response, as reported in previous studies (8,10). In contrast to the study of Jain et al (20), the present study found a significantly higher rate of complete remission with iron therapy in patients with a greater BHS frequency. The complete remission rate was 39.5% (53 patients).…”
Section: Discussionsupporting
confidence: 80%
“…MRI revealed focal cortical dysplasia type I. Video-EEG revealed generalized seizures (both spontaneous and induced by breath-holding) with unclear lateralization. Targeted epilepsy gene panel revealed a de novo previously described pathogenic variant in the SCN8A gene linked to milder phenotypes (20). Our patient had no spontaneous episodes.…”
Section: Discussionmentioning
confidence: 56%
“…For 22, the age at seizure offset was not provided, so they were excluded from subsequent analysis. [8][9][10][11][12][13][14][15][16][17] The remaining 29 cases were combined with our nine individuals (38 total) to assess natural history of seizure progression (Table S1).…”
Section: Combined Cohort (Including New and Published Individuals)mentioning
confidence: 99%
“…61 The EEG findings are variable and depend on the phenotype and include a slow background, multifocal, frontal, temporo-occipital, and generalized epileptiform discharges. 61,63,64 A posterior predominance of epileptiform activity has been observed in some patients. 61 Neuroimaging may show both cortical and subcortical atrophy as well as restricted diffusion in the optic radiations.…”
Section: Scn8amentioning
confidence: 99%
“…63,65 Seizure control may improve in those with gain-offunction mutations (i.e., self-limited familial infantile epilepsy, EIEE) with high doses (supratherapeutic) of sodium channel blockers, such as oxcarbazepine, carbamazepine, or phenytoin. 61,64 The ketogenic diet may also be effective, and in severe cases, levetiracetam may worsen seizures. 61 Synaptic proteins…”
Section: Scn8amentioning
confidence: 99%